Implications of appropriate technology and farm inputs in the agricultural sector of Gujarat: empirical analysis based on primary data - Shah Nawaz Ashraf,; Ajay K Singh, (Agricultural Economics Research Review, 2023)
This study examines the usages, benefits, and obstacles in the applications of various technologies, and the impact of appropriate technologies, on agricultural productivity in Gujarat, India. Most farmers are aware of the economic, social, and environmental viability of appropriate technologies and they use these for a variety of purposes. The results imply that agricultural productivity is influenced by many factors, including technology cost, technological development, total arable land, cropping intensity, irrigated area, use of fertilizer and agricultural labour, annual income of farmers, practice of appropriate technologies in cultivation, financial support from government, agricultural co-operative societies, and agricultural extension offices.